Forest conservation as a CO2 offset measure: a case of an urban development project in Finland - Järveläinen, Mikko; Pihlainen, Sampo; Karhu, Kristiina; Österberg, Nico; Mäkipää, Raisa (Frontiers in Environmental Science, 2024)
This study investigates carbon offset potential in Espoo, Finland, by comparing a constructionimpacted deforestation site with a larger, conserved forest area. Our research quantifies the carbon stock and sequestration impacts, revealing that the conserved forest's (79 ha) carbon stock increased by 26 Mg ha -1 in soil and 65 Mg ha -1 in biomass compared to the baseline scenario. This enhancement is sufficient to compensate for the deforestation site's (19 ha) stock loss of 186 Mg ha -1 and 43 Mg ha -1 , respectively, showcasing forest conservation as a viable method for offsetting carbon stock losses in the context of urban development. This study illuminates the complexities of CO2 compensation regulation and emphasizes the necessity for robust, transparent carbon accounting practices. The insights offer a valuable perspective on integrating nature-based solutions in urban planning to achieve broader ecological and climate goals. This study investigates the carbon offset potential in Espoo, Finland, by comparing a constructionimpacted deforestation site with a larger conserved forest area. Addressing a knowledge gap in localized forest conservation as a CO2 offset method, our research quantifies the carbon stock and sequestration impacts under both baseline and alternative scenarios for the two study sites. The baseline scenario for offset site reflects standard forest management practices, while the alternative scenario involves complete forest conservation without active management. Our findings reveal that the conserved forest (79 ha), dominated by Norway spruce (Picea abies) and Scots pine (Pinus sylvestris), increased its carbon stock by 26 Mg ha-1 in soil and 65 Mg ha-1 in biomass. This enhancement is sufficient to compensate for the smaller deforestation site's (19 ha), also containing a mix of Norway spruce and Scots pine, stock loss of 186 Mg ha-1 in soil and 43 Mg ha-1 in biomass. Furthermore, this study illuminates the complexities of CO2 compensation regulation and emphasizes the necessity for robust, transparent carbon accounting practices. The insights offer a valuable perspective on integrating nature-based solutions in urban planning to achieve broader ecological and climate goals.